PENGARUH SUPLEMENTASI PROPOLIS TEKNOLOGI NANO BAGI PENDERITA TUBERKULOSIS DI RSUD ENDE : - rifatunnisa; Bedho, Martina; Woga, Raimunda (Kelimutu Nursing Journal, 2024)
TB recovery is influenced by a good immune system and drugs and supplements that increase their killing power against Mycobacterium Tuberculosis. One ingredient that can be used as a supplement is propolis. The aim of the research is to prove the effectiveness of propolis with nanoparticle technology as a supplement in curing adult TB. Methodology: This research is an expressive research with a pretest posttest design. The research sample was 7 people with BTA (+) criteria as. The treatment for this research was the administration of TPR propolis (Turkish Propolis Ruqyah) with nano technology at a supplement dose of 1 drop per 10 KgBW. The symptoms felt are observed from the beginning of treatment until after giving therapy at the next control. Sig Value Results. Less than 0.05 is indicated by symptoms of cough accompanied by chest pain (0.031), anorexia (0.031), and decreased weight (0.016). These three symptoms show that there is a significant difference or influence on the symptoms of cough accompanied by chest pain, anorexia, and decreased weight before therapy and after therapy. Meanwhile, the symptoms of fever, malaise and cough with phlegm did not have a significant effect. The results of this study show that TB patients who received OAT therapy accompanied by the provision of nano-technology Propolis supplements were able to reduce the symptoms experienced by patients, namely reducing the symptoms of cough accompanied by chest pain, anorexia, and weight loss did not decrease.